Secular Trends in Prevalence of Overweight and Obesity from 2006 to 2009 in Urban Asian Indian Adolescents Aged 14-17 Years - Gupta, Deepak Kumar; Shah, Priyali; Misra, Anoop; Bharadwaj, Swati; Gulati, Seema; Gupta, Nidhi; Sharma, Rekha; Pandey, Ravindra M.; Goel, Kashish (PloS one, 2011)
The present study examines the secular trends in prevalence of overweight and obesity among urban Asian Indian adolescents in New Delhi (North India). The data were derived from cross-sectional sampling of children, 3493 in year 2006 and 4908 in year 2009, aged 14-17 years studying in privately-funded and government-funded schools. Age, gender and Asian Indian-specific cut offs of body mass index (BMI) were used to define overweight and obesity. The prevalence of obesity increased significantly from 9.8% in 2006 to 11.7% in 2009 (p<0.01), whereas underweight decreased from 11.3% to 3.9% (p<0.001). There was a significantly higher risk of being overweight (OR 1.28; 95% CI, 1.15-1.42) and obese (OR 1.44; 95% CI, 1.24-1.66) in year 2009 than 2006, after adjusting for age, gender and type of school. Males and privately-funded school children had significantly higher increase in prevalence and risk of being overweight and obese over the three years. In conclusion, this study showed an increasing trend in prevalence of overweight and obesity in urban Asian Indian adolescents. More specifically, the study showed the association of this increasing trend of overweight and obesity prevalence with male gender and high socio-economic status, calling for an urgent need for immediate and targeted preventive measures.